Legal Analysis of Bitcoin Ownership as a Medium of Exchange in the Digital Financial System - Gesa Bimantara; Tri Astuti Handayani; M. Aqiel Alam (Yayasan Lembaga Studi Makwa, 2025)
This study examines the legal status and implications of Bitcoin ownership as a medium of exchange within Indonesia's evolving digital financial system. In light of persistent regulatory ambiguity, the research seeks to understand how legal uncertainty shapes the use and recognition of Bitcoin as a transactional asset. Employing a qualitative socio-legal approach, the study integrates doctrinal legal analysis with empirical findings obtained from in-depth interviews with cryptocurrency users, legal scholars, and financial regulators. The findings reveal that Bitcoin ownership in Indonesia lacks formal legal recognition, as there is no existing state-sanctioned registration system or institutional mechanism to validate cryptographic ownership. Instead, the private key remains the only accepted evidence of control and possession, creating a decentralized system of ownership that operates independently from conventional legal doctrines. Despite regulatory restrictions, Bitcoin continues to be used in informal peer-to-peer transactions, primarily driven by user preferences for privacy, decentralization, and efficiency. This disconnect between legal structures and technological realities generates vulnerabilities for users, particularly in cases involving fraud, inheritance, taxation, or contractual disputes, where no formal recourse exists. The research concludes that Indonesia’s legal framework remains ill-equipped to handle the complexities of decentralized financial assets, posing challenges to legal enforceability and consumer protection. The study recommends the establishment of a voluntary, state-recognized digital asset registration system, along with capacity-building initiatives for regulators. These measures aim to enhance legal certainty, bridge institutional gaps, and support the integration of blockchain-based assets into Indonesia’s formal financial and legal ecosystem.